Epilepsy the intersection of neurosciences, biology, mathematics, engineering and physics - Osorio, Ivan. (CRC Press, 2011)
"Integrating the studies of epilepsy, neurosciences, computational neurosciences, mathematics, physics, engineering, and medicine, this volume provides the first means to a clear, structured, and enriching multidisciplinary perspective for developing students, researchers, and clinicians in the field of epilepsy. The text gives up to date information on the state of current research, possible future research, and clinical directions in the fields of epilepsy and seizure dynamics. Clear illustrations that illustrate the patterns of brain electrophysiology and behavioral manifestations are provided to aid comprehension. The authors include extensive references in each chapter to enhance further study"--Provided by publisher.